2005
DOI: 10.1002/ca.20248
|View full text |Cite
|
Sign up to set email alerts
|

Split spinal cord malformation

Abstract: The split spinal cord is a rare congenital malformation. We report the rare finding of a split cord malformation in a young girl. Further evaluation of this anomaly revealed a Type I split cord malformation (midline bony septation), with no other concomitant pathological entities. Various hypotheses have been made regarding the embryology of this unusual form of spinal dysraphism, and these are reviewed along with the common clinical manifestations of this intriguing pathological entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Another theory explains the etiology of anomaly as hyperproliferation of basal cells of the neural tube and then the walls fail to be merged as the result [7]. Figure 3: A: Intraoperative photography confirms the full extension of surgical field containing SCMI at proximal and the SCMII at distal after the bony ridge was removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another theory explains the etiology of anomaly as hyperproliferation of basal cells of the neural tube and then the walls fail to be merged as the result [7]. Figure 3: A: Intraoperative photography confirms the full extension of surgical field containing SCMI at proximal and the SCMII at distal after the bony ridge was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Some other researchers have suggested notochord cleavage as the etiology of SCM. Connection of endoderm and ectoderm as the result of notochord cleavage leads to double neural tube and hemicord formation [7]. Embryonic studies have revealed spinal cord widening at lumbar region and presence of ectodermal groove within two neural tubes in human embryos with diastematomyelia [1].…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Pluripotential cells of the endomesenchymal tract could develop into a variety of tissues consisting principally of mesodermal elements. Several theories have been developed to explain the development of split-cord malformations.…”
Section: Case Report Discussionmentioning
confidence: 99%
“…Recently, one generally accepted theory suggests that split-cord malformations originate from one basic error occurring around the time when the primitive neuroenteric canal closes. The basic error is the formation of an accessory neuroenteric canal between the yolk sac and amnion, which is subsequently invested with mesenchyme to form an endomesenchymal tract that splits the notocord and neural plate [12, 13]. Pluripotential cells of the endomesenchymal tract could develop into a variety of tissues consisting principally of mesodermal elements [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The basic error is the formation of an accessory neuroenteric canal between the yolk sac and amnion, which is subsequently invested with mesenchyme to form an endomesenchymal tract that splits the notocord and neural plate [12, 13]. Pluripotential cells of the endomesenchymal tract could develop into a variety of tissues consisting principally of mesodermal elements [12, 13]. Although the concurrence of a human tail and split cord malformations maybe a mere coincidence, it is tempting to assign a common embryological origin to both events.…”
Section: Discussionmentioning
confidence: 99%